PTU-029 Bowel cancer screening and the use of aspirin and non-steroidal anti-inflammatory drugs (nsaids) – prospective population based analysis. (17th June 2017) - Taha, AS; Diament, RH; McCloskey, C; Craigen, T; Simpson, A; Carrigan, A; Freeburn, L; Angerson, WJ
Abstract : Introduction: Despite being the third most common cancer, after those of the lung and breast, treatment of bowel cancer may have more than 90% success rate if it is detected early. This has prompted many health authorities to invest in bowel screening programmes. AIMS: Given the wide use of aspirin and NSAIDs and their potential effects on gut mucosa, we aimed to compare the bowel-screening colonoscopic findings in users vs. non-users of these agents. Method: In our area – with a population of 370590 – subjects aged 50–74 years were invited to participate in bowel screening. They were provided with guaiac peroxidise faecal occult blood test (gFOBT) kits in order to collect 2 faecal samples from each of 3 bowel movements. The analytical cut-off for the kit was 0.6 mgHb/gm faeces. Patients with positive gFOBT were interviewed and, if agreeable, underwent colonoscopy in one of two endoscopy centres serving our region. The Mann-Whitney test, Fisher's exact test and odds ratios (95% CIs) were used as appropriate. Results: Between January and August 2016, 49 176 subjects aged 50–74 years were sent gFOBT kits, of whom 26 926 completed and returned these kits (54.8% uptake); 598 had positive results (2.2% positivity rate), and these were invited to attend for colonoscopy. The results of 335 patients attending our centre are presented in Tables 1 and 2 below. Conclusion: (1) Bowel cancer screening in our population, using gFOBT, was associated with 54.8% uptake and 2.2% positivity for faecal occult blood. (2) At colonoscopy, the use of aspirin or NSAIDs was associated with fewer patients with big polyps; the polyps were also significantly smaller in size in users of these drugs. Allowing for possible confounding factors, these results might be relevant to bowel screening programmes and to bowel cancer chemoprevention. Disclosure of Interest: None Declared